Implementation of Human Resource Quality Improvement Policies at the Human Resources Development Agency (BKPSDM) of Palangka Raya City - Sulistiyo, Samuel; Rosyidi Yogatama, Habib; Prasetyanto, Ardi; Savera, Felinsia; Klaudia, Friska; Sesar Anikat Putra, M. (Dinasti Publisher, 2024)
One way to enhance employee performance is through employee development via education and training. To achieve the desired performance in an organization, employees must receive adequate training programs for their positions, ensuring they are skilled in their jobs. This study is a descriptive qualitative research, which involves describing empirical phenomena by analyzing and presenting facts systematically to facilitate understanding and conclusions. The analysis of the human resource development program implementation at the Human Resources Development Agency (BKPSDM) of Palangka Raya City reveals several key areas for improvement: 1) Better and more in-depth coordination and consolidation among internal employees and with the Head of BKPSDM; 2) Improved coordination between BKPSDM and external departmental agencies in line with the needs of the Palangka Raya City Government; 3) The need for a comprehensive system to guide the implementation of human resource quality improvement programs, integrated both structurally within the institution and beyond.